DESIGN OF AN INTER-FIRM ELECTRONIC COLLABORATION PLAT-FORM FOR SMES BASED ON AXIOMATIC DESIGN THEORY - Lotchi, Kodjovi Nyalali (My University, 2019)
Small and Medium Enterprises (SMEs) account for 99% of all Businesses in Europe (OECD, 2017). Although having limited resources, they need to compete with bigger institutions. The pressure on the international market force them to find competitive and flexible business solutions. Additionally, due to the digitization of business processes, they need innovative solutions in handling cooperation and networking inside their own company and with their external partners. A notable solution is to seek for opportunities to cooperate with other organizations and to become part of a business network (Casals, 2011: 118–124). This thesis, which is part of EU funded Pisku project, explores the underlying needs that SMEs face when they strive to engage in inter-firm collaboration. It also aims at design-ing a prototype of an electronic inter-firm collaboration platform to support their busi-ness processes. A mixed strategy research method that includes qualitative and axiomatic design theory is used. The theoretical framework analyses the SMEs collaboration in a digital area and how it affects their performance and growth. It also highlights internal and external rea-sons to collaborate and the collaboration process framework as well. The empirical part consists of questionnaire designed for the SMEs participating in the project. The aim of the questionnaire is to identify their challenges in general and their needs regarding an inter-firm collaboration platform by using mainly the axiomatic de-sign theory. The finding of this research is divided into two parts. The first part is to identifies and list the needs and challenges faced by SMEs when collaborating. The second part con-sists of mapping these needs into requirements and parameters to design an inter-firm e-collaboration platform.
Keywords: Inter-firm collaboration; Intra-firm collaboration; Axiomatic design; Collaboration plat-form; E-collaboration; SME; fi=Master's Degree Programme in Industrial Management|